LOS SUEÑOS DE LOS GESTORES DEL ESPACIO PÚBLICO ENGENDRAN MONSTRUOS AMBULANTES - Contreras, Anabelle (2015)
This book review is the public presentation by PhD Anabelle Castro Contreras of the book “Cartografías josefinas: Ventas ambulantes y espacio público” made during the month of November 2013 at the School of Architecture, the University of Costa Rica. The author analyzes the core ideas by frame them into their urban, cultural and political context. In doing this, Contreras links the content of the publication with the historical and contemporary situations of public space in the city of San Jose, Costa Rica.